PENGARUH PEMAKAIAN OBAT ANTIEPILEPSI JANGKA PANJANG TERHADAP DENSITAS TULANG DAN KADAR ALKALI FOSFATASE PADA PENDERITA EPILEPSI YANG BEROBAT DI POLIKLINIK SARAF RS DR M DJAMIL PADANG - Meiti Frida* (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND EPILEPSY IS A HEALTH PROBLEM THAT COULD BE HAVE IMPACT MEDICAL SOCIAL PSYCHOSOCIAL AND ECONOMIC STATUS IN THE COMMUNITY EPILEPSY THERAPY IT SELF MAY HAVE RESULT IN MANY PROBLEMS EITHER WHICH WERE ASSOCIATED WITH LONGTERM THERAPY AND OTHER ASPECTS GENERAL PRINCIPLE OF EPILEPSY THERAPY IS TO KEEP PATIENTS IN A NONCONVULSION STATE WITHOUT ANY SIGNIFICANT ADVERSE EFFECTS TAKING ANTIEPILEPTIC DRUGS IN THE LONGTERM PERIODS COULD BE AFFECT BONES DECREASING BONE MINERAL DENSITY AND INCREASING ALKALINE PHOSPHATASE LEVEL